Every Man his own Electric Physician: T. Gale and the History of Do-It-Yourself Neurology - Erika, L. Janik; Matthew, B. Jensen (Journal of Neurological Research And Therapy, 2016)
We review the promotion of electrical treatments by laypeople for neurological and other conditions in a largely rural period of United States history.
Keywords: neurology; history; electricity.